Editorial: Islam and Human Rights, Contested Viewpoints (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2007)
The remaining problem faced by Muslims living in this modern life is how the teachings of Islam believed as bless for all human being can be confirmed in the reality of everyday life humanity crammed with conflicts and dissonances. It is staggering to consider that not all Muslims concern, and perhaps do not wish to know, about the current discourse on Islam and its relation with others. Although Samuel Huntingtonâs controversial theory of âClash of Civilizationâ might be challenged by most Muslim circles, the heightening conflict involving Western and Islamic civilizations in the aftermath of September 11, 2001 has approved his theory. The attack of terrorism to the US soil has triggered not only the unremitting war on terror undergone towards the alleged Muslim terrorists worldwide but also the worsening relationship between the two civilizations believed to have been engulfed since the two decades before. Candidly, this phenomenon has also affected the intra-faith dialogue among Muslims having different thought of religion.